Promoção da segurança no cuidado de enferamgem pediátrica: contribuições para o ensino técnio - Nascimento, Juliana da Silva Garcia [UNESP] (2014)
The present study addresses the promotion of safety in the care of hospitalized children, electing as object teaching of this topic in nursing technical courses. The objective of elaborating systematic proposals to subsidize the planning of nursing technical teaching about promoting safety in the care of hospitalized children, based on specialized literature and from the perspective of active teachers in technical schools public nursing in the State of São Paulo – Brazil. Initially, integrative literature review was performed on errors, adverse events and safety promotion measures for hospital and its approach in pediatric nursing technical teaching. In the review were included 17 full papers, published January 2001 to December 2012, on nine national and eight international journals, and most of the early authors was of nurses and 15 of them have used quantitative research approach. Descriptive analysis was conducted of the data were categorised: types of errors and adverse events related to pediatric hospitalization, measures to promote patient safety in children, strategies for the inclusion of the theme of promoting patient safety in nursing formal education. Subsequently, under the qualitative research approach, semi-structured interviews was applied to 10 teachers from six schools public nursing techniques do Estado de São Paulo, linked to the Paula Souza Centre. The evidence collected were organized according to the thematic aspects of the method of content analysis, being the same analyzed according to the postulates of Paulo Freire. The themes and their respective nuclei of meaning were: Theme 1-safety of children admitted to hospitals: Children in hospitalization are exposed to different types of errors and adverse events; The team must have health profile and be able to prevent errors and adverse events with children; There must be the institutionalization of measures to promote ...